Pengaruh ROA ROE Terhadap Harga Saham Pada PT. Blue Bird Tbk dan PT. Transportasi Indonesia Tbk - Rizki Kumala; Wardayani Wardayani (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether Return on Asset and Return on Equity simultaneously and partially affect stock prices in transportation companies PT. Blue Bird Tbk and PT. Transportasi Indonesia Tbk (WEHA) listed on theBursa Efek Indonesia. The population and sample in this study are the company's financial statements PT. Blue Bird Tbk and PT. Transportasi Indonesia Tbk (WEHA) listed on the Bursa Efek Indonesia of the year 2015-2019. The data used are secondary data. The analysis technique used is statistical analysis and multiple linear regression test.Based on the test results it can be concluded thatReturn on Asset (ROA) and Return on Equity imultaneously and significantly influence the stock price.Partially Return on Asset (ROA) have effect and significantly on stock prices and Return on Equity (ROE) has no and significant effect on stock prices.